PERLINDUNGAN HUKUM KONSUMEN DALAM JUAL BELI KENDARAAN BERMOTOR RODA DUA SECARA KREDIT PADA PT FEDERAL INTERNATIONAL FINANCE (FIF) DI SAMARINDA - Wahyuni Safitri (Law Department, University of Widya Gama Mahakam Samarinda, 2009)
This was a normative-judicial research on consumer legal protection in purchasing motorcycles by instalment through Federal International Finance (FIF) in Samarinda. It was aimed at investigating to what extend the purchasing of motorcycles by instalment through FIF is legally protected. The research collected both primary and secondary data. The primary data was collected by field survey conducted through semi-structured interview, while the secondary data was obtained by means of literature review. It was concluded, firstly, that the position of consumers in making instalment credits for motorcycles at FIF Samarinda was very weak. This was because the sale contract or credit agreement has been prepared in advance by the FIF. Legally, such a condition is acceptable because FIF is having good faith based on consumers’ agreement as stipulated in Article 1320 of KUH Perdata. Secondly, whenever the objets of the contract or agreement were in force majeure condition, the consumers were hardly protected.